2021
DOI: 10.1200/jco.21.00482
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Evaluate the Electronic Patient-Reported Outcome Appropriately?

Abstract: Absolom et al 1 reported that the use of electronic patient self-Reporting of Adverse-events: Patient Information and aDvice (eRAPID) improved patients' physical health at 6 and 12 weeks of treatment and self-efficacy at 18 weeks. The patient-reported outcome (PRO) is an essential indicator in current clinical trials. Although the usefulness of electronic PRO (ePRO) for patients with cancer with distant metastases has been shown, 2,3 this study is epoch-making because it showed the effectiveness of ePRO in pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In addition, the questionnaire to monitor symptoms was specifically designed for melanoma patients receiving CPI(s) [ 21 ], precisely assessing the toxicities they may experience as recommended by Kluetz et al [ 35 ]. Shojima et al [ 36 ] also argue that AEs vary across treatment regimens, making it difficult to evaluate them. In our study, all patients had melanoma and were treated with drugs with the same toxicity profile, substantial strengths in studying AEs among patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the questionnaire to monitor symptoms was specifically designed for melanoma patients receiving CPI(s) [ 21 ], precisely assessing the toxicities they may experience as recommended by Kluetz et al [ 35 ]. Shojima et al [ 36 ] also argue that AEs vary across treatment regimens, making it difficult to evaluate them. In our study, all patients had melanoma and were treated with drugs with the same toxicity profile, substantial strengths in studying AEs among patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Data management is a tremendous challenge, but the advent of digital transformation may lead to the disruption of current practices and will revolutionize healthcare in the decade to come. There is still an ongoing debate on whether PROMs are being assessed on paper versus electronically; although, it has been shown that the latter far exceeds the potential disadvantages, and manual analysis of paper PROMs is not affordable anymore given the current overall labor shortage [ 9 , 54 , 55 , 56 ].…”
Section: Interoperable Digital Platform: Data Assessment and Analysismentioning
confidence: 99%
“…Shojima et al 1 have provided comments and questions on our recent publication, 2 where we demonstrated that an electronic patient-reported outcome–based intervention, called eRAPID electronic patient self-Reporting of Adverse-events: Patient Information and aDvice (online patient reporting of disease- and treatment-related symptoms during chemotherapy, supplemented by an immediate severity-tailored patient advice) improved patient physical well-being early during the course of treatment (6 and 12 weeks) in a mixed population of 508 patients with cancer. The impact was in patients treated with curative intent (two thirds of the sample) and in those experiencing mild to moderate symptoms.…”
mentioning
confidence: 99%
“…Shojima et al 1 expressed concerns over the variability of the patient population (early and metastatic disease; breast, colorectal, and gynecologic cancers; types and duration of chemotherapy; and duration of adverse events beyond 18 weeks of the trial). These are valid points and have been considered carefully during the design of eRAPID intervention and the randomized trial.…”
mentioning
confidence: 99%